A critical analysis of Madanpal Nighantu - An ancient lexicon of Ayurvedic literature - Karuna; Swati Arya; Rajesh Kumar Mishra (Wolters Kluwer Medknow Publications, 2023)
Since ancient times, there is a tradition of composition of lexicons in Ayurveda, which are called Nighantu. The Ayurvedic physicians who do not know the names of drugs, they become suspicious and do not recognize the medicine even after seeing. We gain this knowledge from Nighantu, so the study of Nighantu is essential for Ayurvedic physicians. In the tradition of Ayurvedic lexicons, Madanvinod/Madanpal Nighantu is a sophisticated treatise of Dravya-guna. It is composed by Nrip Madanpal in 1374 A. D. This lexicon has thirteen varga (sections) and at the end Granthakartriprashasti, 14th section is mentioned. In this treatise, along with ancient medicinal substances, new substances like Ahifen are also described. Objective: The objective is to study and analyze the importance and utility of Madanpal Nighantu, in the illumination of the knowledge of handwritten manuscripts. Data Source: Preprinted versions and handwritten manuscripts of Madanpal Nighantu, contemporary journals, articles, internet material, and previous research papers related to these subjects have been used. Review Methods: All the published and unpublished literature related to Madanpal Nighantu is reviewed by comparing and analyzing the different meanings and thoughts of classical as well as contemporary authors. A separate analysis of commentaries on classical texts is done for better understanding. Result and Conclusion: This article highlights the utility and importance of handwritten manuscripts for the sophistication of Madanpal Nighantu. By which the identification, properties and actions of drugs and medical treatment can be made more effective and powerful.